Association of high-density lipoprotein and myocardial infarction: a cross sectional study - Thirupathi, Siraveni; P., Chinnaiyan; Chandrababu, Sujeetha (International Journal of Advances in Medicine, 2019)
Background: There is substantial evidence illustrating a negative relationship between High Density Lipoprotein Cholesterol (HDL-C) to Coronary Artery Disease (CAD) progression. HDL concept can be put forward as a new concept in the field of cardiovascular research. The objective of this study was to carry out to observe the status of serum HDL-C level in Coronary Artery Disease patients and the impact of the level in them. Methods: It was a hospital based cross sectional observational study among 60 patients of acute myocardial infarction (MI) who were admitted in Medical intensive care unit. High density lipoprotein cholesterol (HDL-C) was determined using standard methods. Results: The study showed that 52 (86.7%) of study subjects had abnormal HDL-C level and 39 (65%) of subjects had abnormal CRP level. There is a negative correlation between HDL and other biochemical variables like LDL, LDL/HDL and CRP, i.e. as HDL decreases all the variables increase which is statistically significant. Majority of patients 52 (86.7%) with MI had abnormal HDL-C level which was not statistically significant. Conclusions: Numerous studies showing evidence that high levels of HDL-Cholesterol associated with a lower risk of Coronary heart disease. This study showed that there is a low HDL-C level among coronary artery disease patient. The relationship between HDL and CAD proved to be an inverse one which caters the need to concentrate further on HDL.